Evaluación de la producción de células de la línea celular de leucemia linfocítica aguda de humano (REH) en un biorreactor spinner de 250 mililitros (2019)
The purpose of this project is to evaluate the escalation of the production of acute human lymphocytic leukemia (REH) cells, in order to obtain maximum concentrations of these, since they serve as host cells for WT1-5 oncolytic virus replication, which causes childhood gastroenteritis. The scaling was worked from 24-well microplates, followed by the experiment in Petri dishes, where both kinetics were evaluated for growth kinetics and cell viability, in order to obtain data such as the specific growth rate and the time it takes for the cells to double. The respective experiments were then carried out in the 250 mL spinner reactor, where, in addition to evaluating the growth kinetics and its viability, glucose consumption data were obtained in each sample that was used to make the respective cell count, reaching show a relationship between glucose consumption and cell concentration. Subsequently, a simulation of the 250 mL spinner reactor is carried out in the MATLAB open source program, where the results achieved are they compare with the data obtained experimentally. At the end of each of the experiments, the cells that grew in a Petri dish and in the 250 spinner reactor were delivered for the subsequent infection and production of the WT1-5 virus named above.